Comparative genomics of Deinococcus radiodurans: unveiling genetic discrepancies between ATCC 13939K and BAA-816 strains - Jeong, Soyoung; Singh, Harinder; Jung, Jong-Hyun; Jung, Kwang-Woo; Ryu, Sangryeol; Lim, Sangyong (Frontiers in Microbiology, 2024)
The Deinococcus genus is renowned for its remarkable resilience against environmental stresses, including ionizing radiation, desiccation, and oxidative damage. This resilience is attributed to its sophisticated DNA repair mechanisms and robust defense systems, enabling it to recover from extensive damage and thrive under extreme conditions. Central to Deinococcus research, the D. radiodurans strains ATCC BAA-816 and ATCC 13939 facilitate extensive studies into this remarkably resilient genus. This study focused on delineating genetic discrepancies between these strains by sequencing our laboratory's ATCC 13939 specimen (ATCC 13939K) and juxtaposing it with ATCC BAA-816. We uncovered 436 DNA sequence differences within ATCC 13939K, including 100 single nucleotide variations, 278 insertions, and 58 deletions, which could induce frameshifts altering protein-coding genes. Gene annotation revisions accounting for gene fusions and the reconciliation of gene lengths uncovered novel protein-coding genes and refined the functional categorizations of established ones. Additionally, the analysis pointed out genome structural variations due to insertion sequence (IS) elements, underscoring the D. radiodurans genome's plasticity. Notably, ATCC 13939K exhibited a loss of six ISDra2 elements relative to BAA-816, restoring genes fragmented by ISDra2, such as those encoding for α/β hydrolase and serine protease, and revealing new open reading frames, including genes imperative for acetoin decomposition. This comparative genomic study offers vital insights into the metabolic capabilities and resilience strategies of D. radiodurans.